Attitudes towards asylum seekers: Evaluating a mature-aged community education programme - Hartley, Lisa; Pedersen, A.; Dandy, J. (Trentham Books Limited, 2012)
The arrival of asylum seekers and refugees across a nation’s border is often the subject of contested debate in many Western nations. Australian research finds unacceptable levels of community prejudice against asylum seekers (e.g., Klocker, 2004; Suhnan et al., in press). Compared to other Western nations, Australia receives relatively few asylum seekers. For example, the UNHCR (2011) finds that of the top 15 receiving Western countries, Australia is ranked 13th. Despite Australia’s comparatively small number of asylum applications, those who arrive unauthorised (i.e., without a valid visa) are subject to mandatory detention whereby they are held in an immigration detention centre until they receive a visa and security clearance; sometimes this can take years (Briskman et al., 2008). There is considerable evidence showing that mandatory detention has an extremely detrimental effect on asylum seekers’ mental health (e.g., Davidson et al., 2008; The Australian Psychological Society, 2011).